Bronchial thermoplasty and the role of airway smooth muscle: are we on the right direction? - Menzella F; Lusuardi M; Galeone C; Facciolongo N (Dove Medical Press, 2017)
Francesco Menzella,1 Mirco Lusuardi,2 Carla Galeone,1 Nicola Facciolongo1 1Department of Medical Specialties, Pneumology Unit, IRCCS – Arcispedale Santa Maria Nuova, Reggio Emilia, 2Unit of Respiratory Rehabilitation, AUSL Reggio Emilia, S Sebastiano Hospital, Correggio, Italy Abstract: Asthma is characterized by inflammation of the airways that includes eosinophils, basal membrane thickening, epithelial sloughing, vascular changes, smooth muscle hypertrophy and hyperplasia, and mucous gland hyperplasia. Recently, there have been studies on the role of hypersensitivity and inflammation in asthma, but the role of bronchial smooth muscle remains unclear. Bronchial thermoplasty is an endoscopic procedure that is approved by the US Food and Drug Administration (FDA) for the treatment of severe refractory asthma, based on the local delivery of radio frequency at 65°C to the airways, with the aim of controlling bronchospasm through a reduction of airway smooth muscle (ASM). Several recent studies have shown significant improvement in clinical outcomes of bronchial thermoplasty for asthma, including symptom control, reduction in exacerbation and hospitalization rates, improved quality of life, and reduction in number of working days or school days lost due to asthma. Data from these recent studies have shown reduction in ASM following bronchial thermoplasty and changes in inflammation patterns. It has also been argued that bronchial thermoplasty may have modulating effects on neuroendocrine epithelial cells, bronchial nerve endings, TRPV1 nerve receptors, and type-C unmyelinated fibers in the bronchial mucosa. This may involve interrupting the central and local reflexes responsible for the activation of bronchospasm in the presence of bronchial hyperreactivity. Several questions remain regarding the use of bronchial thermoplasty, mechanism of action, selection of appropriate patients, and long-term effects. In this review, the role of ASM in the pathogenesis of asthma and the key aspects of bronchial thermoplasty are discussed, with a focus on the potential clinical effects of this promising procedure, beyond the reduction in ASM. Keywords: airway, nerve, receptors, asthma, inflammation